The Potential of Red GEDI Leaf Extract (Abelmoschusmanihot L) as an Alternative Change in Blood Pressure in Postpartum Mothers with Hypertension - Triany Laila Pelu (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Background Hypertension is the most common non-communicable disease found during pregnancy, childbirth and childbirth. The dangers of hypertension include the emergence of pain in the chest, metabolic syndrome, tend to be easily irritated, disorders of the kidneys, hypertensive retinopathy, stroke resulting in an increased risk of morbidity and mortality. Half to two thirds of women with postpartum hypertension diagnoses are preeclampsia and eclampsia. The administration of antihypertensive chemical drugs such as diuretics, ace-inhibitors, beta blockers and ca blockers, contains many risks, while treatment by providing natural ingredients with minimal negative effects. One of the natural ingredients of medicinal plants for hypertension is red gedi leaf extract (Abelmoschus manihot L). Red gedi leaves contain flavonoids from flavanones and flavanols which act as antihypertensive agents. Objective Proving the administration of red gedi leaf extract (Abelmoschus manihot L) as an alternative change in blood pressure in postpartum mothers with hypertension Methods This research is a quantitative study with a quasi-experimental design with a pre-test and post-test controlled group design. The number of samples is 30 respondents. The respondents of the intervention group were 15 respondents and the control group was 15 respondents. In the intervention group the administration of red gedi leaf extract (Abelmoschus manihot L) dose of 480 mg, 1x2 capsules (each capsule 240 mg) and antihypertensive drugs nifedipine dose 10 mg, 3x1 tablets for 7 days in the intervention group. Whereas in the control group administration of antihypertensive drugs nifedipine dose 10 mg, 3x1 tablets and placebo 1x2 capsules for 7 days. Results The treatment group's systolic blood pressure drops 10 to 21 mmHg, the diastolic pressure drops 6 to 11 mmHg. The decrease in systolic blood pressure in the control group dropped by 1 to 11 mmHg, the diastolic pressure dropped from 0 to 9 mmHg. The bivariate analysis of systolic blood pressure before treatment was p = 0.595 (>0.05) and after intervention was p = 0.000 (<0.05). The results of bivariate analysis of diastolic blood pressure before treatment were p = 0.897 (> 0.05), after intervention was given p = 0.00 (<0.05). Conclusions and Recommendations Giving red gedi leaf extract (Abelmoschus manihot L) for 7 days has the potential to reduce systolic and diastolic blood pressure. Able to do more similar research with respondents and varying doses, can also check hormone levels that play a direct role in changes in blood pressure such as the hormone cortisol, betaendhorpin or adosterone. Future studies can control external factors that affect changes in blood pressure.